Community-Based Pharmacists' Needs for HIV-Related Training and Experience. (August 2014) - Kibicho, Jennifer; Pinkerton, Steven D.; Owczarzak, Jill
Objective: To examine pharmacists' self-reported competence in providing care to persons living with HIV (PLWH) and their HIV-related training and experience needs. Methods: We interviewed 28 community-based pharmacists providing care to PLWH in 4 Midwestern cities. Results: Less than half (46%) of the pharmacists considered themselves competent to provide PLWH care, and less than a third (29%) worked with PLWH during their pharmacy residency. Specialty pharmacists need training on opportunistic infections and HIV-related comorbidities, nonspecialty pharmacists need general training in HIV treatment and patient communications skills, and all pharmacists require a mechanism to keep updated in the latest HIV treatment recommendations. Conclusion: In the current era of patient-centered care, a pharmacist that is well rounded—not just in dispensing antiretroviral medications but highly knowledgeable in different aspects of ART and HIV-specific patient care—can make a valuable contribution to the health care team. Pharmacy school curricula and continuing professional education need to be aligned to meet the knowledge and competency needs of community pharmacists who are strategically positioned to provide care to PLWH.